Stage-specific action of Runx1 and GATA3 controls silencing of PU.1 expression in mouse pro–T cells - Hosokawa, Hiroyuki (J Exp Med, 2021)
PU.1 (encoded by Spi1), an ETS-family transcription factor with many hematopoietic roles, is highly expressed in the earliest intrathymic T cell progenitors but must be down-regulated during T lineage commitment. The transcription factors Runx1 and GATA3 have been implicated in this Spi1 repression, but the basis of the timing was unknown. We show that increasing Runx1 and/or GATA3 down-regulates Spi1 expression in pro–T cells, while deletion of these factors after Spi1 down-regulation reactivates its expression. Leveraging the stage specificities of repression and transcription factor binding revealed an unconventional but functional site in Spi1 intron 2. Acute Cas9-mediated deletion or disruption of the Runx and GATA motifs in this element reactivates silenced Spi1 expression in a pro–T cell line, substantially more than disruption of other candidate elements, and counteracts the repression of Spi1 in primary pro–T cells during commitment. Thus, Runx1 and GATA3 work stage specifically through an intronic silencing element in mouse Spi1 to control strength and maintenance of Spi1 repression during T lineage commitment.